Politics and reformations : histories and reformations : essays in honor of Thomas A. Brady, Jr. - Ocker, Christopher; Brady, Thomas A., Jr., 1937- (Studies in medieval and Reformation traditions, 2007)
These twenty-three essays explore the historiographies of the Reformation from the fifteenth century to the present and study the history of religion from the sixteenth to eighteenth centuries, especially in Germany but also in Switzerland, the Netherlands, and colonial Mexico.